Genotype x Environment interaction studies in different clones of poplar (Populus deltoides Bartr. ex Marsh) - Verma, R.C.; Bangarwa, K.S. (Indian Journal of Agroforestry, 2020)
The present investigation on Genotype x Environment interaction was carried out under nursery conditions in sixty clones of Populus deltoides obtained from WIMCO and State Forest Department. The P. deltoides cuttings were planted during third week of January 2000 (E1), third week of January 2001 (E2) and second week of February 2001 (E3). The data on growth characters like sprouting percentage, survival percentage, total height, basal diameter, unbranched height, inter nodal length, number of branches and tapering was recorded. The pooled regression analysis conducted for GxE interaction and stability analysis revealed the presence of enough variability among the clones for various characters. The linear type of G x E (b) was observed in sixteen clones. The non linear type of G x E interaction (S-2 d) were observed in ten clones. Both linear and non linear type of G x E interaction were observed in five clones for total height. Clone number 171 was found to be an ideal genotype for total height (x=7.02 m) near to unit regression (b=0.81) and non significant (S-2 d). For basal diameter clone 156 obtained from WIMCO was found the most suitable and ideal clone (x= 6.44 cm) nearly unit regression (b=1.02) and non significant (S-2d).